Village Financial Management, Labor Absorption and Village Community Welfare - Abdul Hadi Sirat; Abdul Rahman Jannang; Irmawati Tjan (Atestasi : Jurnal Ilmiah Akuntansi, 2022)
This research aims to examine and evaluate how village financial management, employment, and community welfare are planned and executed through village funds, and the impact of managing village funds on improving the well-being of rural communities in South Halmahera Regency. The research employs a qualitative method, where researchers conduct interviews with key informants, including village officials, BPD, and community members. Data is collected through interviews, observation, and documentation, and analyzed using a descriptive qualitative method. Results indicate that overall, the management of village funds in South Halmahera Regency is not effective, as evidenced by a lack of community participation in the management process and inadequate administration, reporting, and accountability of village finances. Additionally, village funds are not being utilized to their fullest potential, and there are obstacles such as delays in APBDes approval and submission of accountability reports. The Village Government also needs to improve on informing the community about proper use of village finances. The village financial management also faces challenges in terms of human resource competence, necessary facilities, and access to technology.